Incremental cost of treating antimicrobial-resistant infections among hospitalised patients in India: a cohort study - Sanjay M Mehendale; Kamini Walia; Pallab Ray; Nusrat Shafiq; Shankar Prinja; Sagar Khadanga; Susmita Chatterjee; Raman Gangakhedkar; Samiran Panda; Sanjay Bhattacharya; Megha Mamulwar; Abhijit Kadam; et al. (BMJ Open)
Background Accurate estimates of incremental cost (IC) attributable to antimicrobial resistance (AMR) provide information of immense public health importance to the policy makers. Here, we present the IC from patient perspective for treating antimicrobial-resistant pathogens in India.Methods This cohort study was conducted in eight hospitals including government (GH), private (PH) and trust hospitals (TH), considering their ownership, geographical location and categories of cities. This study had a retrospective component, which calculated the direct cost of treating resistant and susceptible blood stream infections caused by selected WHO priority pathogens. The prospective component estimated indirect cost and financial coping strategies for the treatment of AMR. In the retrospective component, 1723 records were included and 170 patients were recruited in the prospective component.Results The median total cost for management of antimicrobial-resistant infections was US$199 (IQR 89, 377) as opposed to US$109 (IQR 55, 229) for susceptible infection in GH. Our study has revealed that the ICs for Enterobacteriaceae (53.9%), Acinetobacter (43.8%) and Staphylococcus (49.7%) at GHs were higher for resistant pathogens. Pharmaceutical cost was the major contributor to IC at GHs (61.5%) and PHs (27.1%). In the prospective component, 46.5% of patients resorted to borrowing money for hospitalisation expenses and the per day median total cost for resistant and sensitive infection was estimated to be US$65 and US$35, respectively.Conclusions The current study concluded that the presence of any critical or high priority pathogens led to an increase in the direct and indirect medical costs. The IC varied with hospital type, length of stay, pathogen, comorbidities and diagnosis. Prospective studies are needed for precise understanding of variations in the costs of treating AMR infections.